2016
DOI: 10.1111/hepr.12692
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and prognosis of patients emergently hospitalized for acute esophageal variceal bleeding: A long‐term cohort study

Abstract: This study revealed more than 50% cumulative rebleeding and mortality in the 5-year period after endoscopic variceal ligation for esophageal variceal bleeding in an emergency setting. Child-Pugh C, alcoholic liver cirrhosis, and no follow-up endoscopy increased the risk of rebleeding; Child-Pugh C, coexistence of hepatocellular carcinoma, and no follow-up endoscopy increased the risk of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
2
19
1
Order By: Relevance
“…In addition, hepatocellular carcinoma was also an independent risk factor for 6-week mortality of EVH post EVL according to multivariate hazard Cox analysis with parameters of scoring systems included. This finding was the same as previous studies, and portal thrombosis induced advanced portal hypertension was suggested as the reason[ 21 23 ]. So, the cut-off point for predicting 6-week mortality was different after subgroup analysis according to with or without a history of hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, hepatocellular carcinoma was also an independent risk factor for 6-week mortality of EVH post EVL according to multivariate hazard Cox analysis with parameters of scoring systems included. This finding was the same as previous studies, and portal thrombosis induced advanced portal hypertension was suggested as the reason[ 21 23 ]. So, the cut-off point for predicting 6-week mortality was different after subgroup analysis according to with or without a history of hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…The number of endoscopy sessions required to achieve variceal eradication has varied considerably within reported series and between centers (Table 5 ). A number of studies, including a meta-analysis by Ko et al[ 18 , 38 - 42 ] indicated that EVL achieved variceal eradication rates between 79% and 100%. While there is some evidence to suggest that the methodology and technique of EVL might affect the number of sessions necessary to achieve obliteration, this alone does not explain the substantial differences found between patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 mmHg, are at risk of developing gastroesophageal varices. Despite improvements in diagnostics and therapy over the last decades, variceal bleeding still is life-threatening with a 6-week mortality of 10-20% [2,12,13]. In this regard, recent studies indicate that transient elastography is a promising non-invasive screening method for detecting decompensated PH, suggesting a direct positive correlation between spleen and liver stiffness and esophageal variceal bleeding [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Five patients were male (56%). The mean Child-Pugh Score at the time of spleen embolization was 5.9 ± 1.3 [5][6][7][8] points, the mean MELD-Score 8.9 ± 2.6 [6][7][8][9][10][11][12][13][14]. All patients had splenomegaly with a mean spleen diameter of 16.6 ± 2.8 [13.3-22.3] cm.…”
Section: Patient Characteristicsmentioning
confidence: 99%